Adenoid Cystic Carcinoma of the Lacrimal Gland Metastasizing after a Short Followup to Multiple Distant Bones - a Case Report with a Review of the Literature (Faridpur Medical College Journal, 2016)
Adenoid cystic carcinoma (ACC) of the lacrimal gland is a rare disease, but it is the most common malignant epithelial tumor of the lacrimal gland, with poor prognosis. ACC of the lacrimal gland is notorious for its slow growth and tendency to recur despite surgical therapy and following radiotherapy and/or chemotherapy. This tumor type occasionally metastasize via haematogenous spread to lungs, brain and bone in decreasing order of frequency. When it happens, metastases are always multiple and wide. We report a case of a 28-year young man followed in our Hospital with ACC of right lacrimal gland resected on April 2014 and treated with surgery followed by post-operative radiotherapy (50Gy total dose). After one years of follow-up, Positron Emission Tomography (PET) scan reported multiple lytic lesions in distant bones specially to multiple sites of vertebral column. Fine Needle Aspiration Cytology (FNAC) confirmed metastasis of ACC. No evidence of other loco-regional or distant metastasis were described. Patient was treated with chemotherapy. After treatment, patient is actually in close follow up.Faridpur Med. Coll. J. Jul 2015;10(2): 84-86